A tough, stretchable, and extensively sticky hydrogel driven by milk protein. Issue 19 (18th April 2018) - Xu, Jianyu; Fan, Ziwen; Duan, Lijie; Gao, Guanghui
Abstract : A tough and adhesive hydrogel assisted by milk protein was proposed, which could adhere to diverse surfaces of various materials. Abstract : For hydrogels, toughness and adhesiveness are contradictable. However, the simultaneous requirement for both is very urgent in some practical applications, such as robotic joints, wound dressing, and surgical bandages. Herein, milk casein as a protein model was introduced into polyacrylamide (PAAm) hydrogel, which resulted in adequate adhesiveness and mechanical strength. Surprisingly, casein-PAAm hydrogel could repeatedly adhere to the surface of various solid materials and biological tissues by possible physical interactions. A maximum peeling force of 378 N m −1 for casein-PAAm hydrogel on an aluminum surface was measured. Moreover, casein-PAAm hydrogel exhibited adequate mechanical performance with fracture stress of 180 kPa at fracture strain of 2000%. Therefore, the strategy based on tough and adhesive hydrogels assisted by protein would broaden the direction to fabricate a new generation of soft materials with multiple adhesive properties and tough mechanical properties.